Aspek Konstitusional Pengadaan Tanah Untuk Pembangunan Kepentingan Umum - Baso Madiong (Universitas Atma jaya Makassar, 2011)
The Prinsiple of the land acqusition for construction of public interest since the beginning set in the regulation of the Minister Home Affair No. 15 in 1975 until the endorsement of Perpres (Presidential Regulation) No. 65 in 2006, Regarding the deliberation grant restitusions causes legal controversi. ..................